EKSISTENSI PEMBIAYAAN MULTIJASA DI BAITUL MAAL WATTAMWIL - Dewi Rahmawati; Abdul Mujib (ITB AAS INDONESIA Surakarta, 2023)
The development of products in Islamic financial institutions is increasingly widespread. In order to develop a product, Islamic financial institutions must be guided by sharia principles. One form of product development at BMT is multiservice financing. The implementation of this multiservice financing uses an ijarah contract. The emergence of this new product also raises new problems regarding compliance with contract provisions. This study uses a qualitative method, with a normative juridical approach. This type of research is literature study. The results of this study indicate that multiservice financing is a product that is needed by the community and is a reliable alternative for BMTs. However, its implementation is not in accordance with sharia principles